Evaluating Office Equipment Maintenance Practices in a Trading - lutvhiana Putri Muzaki Kholifatul Hikmah; Azis, Aminudin (Politeknik Negeri Madiun, 2024)
The high intensity of office machine usage can lead to a decline in machine performance, thereby requiring proper maintenance to ensure operational reliability. PT INKA Multi Solusi Trading Madiun places significant attention on office machine maintenance to minimize potential disruptions. This study aims to describe and analyze the utilization of resources in office equipment maintenance activities at the company. The research applies a descriptive qualitative method with data collection through interviews, observations, and documentation. The findings reveal that office machine maintenance at PT INKA Multi Solusi Trading utilizes various resources, including manpower, money, materials, machines, methods, and minutes. Labor is allocated according to competence with a clear division of tasks and workload, while maintenance costs are included in operational expenses. The availability of materials and tools is adequately maintained to support both preventive and corrective maintenance, such as inspection, cleaning, storage, repair, and replacement. Furthermore, the scheduled maintenance plan is implemented effectively and efficiently, resulting in positive impacts on office machine performance and operational continuity. Keywords: